MARKETING PLAN BISNIS RUKO “AP EXPRES” - Rosada, Amalia (Jurnal Teknologi dan Bisnis, 2020)
This study aims to determine the feasibility of a shop business marketing plan. The feasibility of this investment is analyzed through a marketing plan that is reviewed from market and marketing aspects, and by considering the financial aspects through an analysis of Payback Period, Net Present Value and Profitability Index. The results of the qualitative and quantitative analysis show that De Medows’ marketing plan is acceptable and feasible to implement